Granulation tissue enriched by aspirin and omega-3 fatty acids in healing experimental periodontal lesion - Hromcik, Filip; Vokurka, Jan; Gopfert, Eduard; Faldyna, Martin; Hermanova, Marketa; Kyr, Michal; Vicenova, Monika; Izakovicova Holla, Lydie (Biomedical papers, 2021)
Aims. Granulation tissue (GT) and specialized pro‑resolving mediators such as lipoxins and resolvins are key elements in the successful resolution of periodontitis. Aspirin‑triggered lipoxins and resolvins are even more powerful than their natural analogues. Their biosynthesis can be accelerated by omega-3 fatty acids. The aim of this study was to evaluate the use of GT enriched by aspirin and omega-3 fatty acids during the surgical treatment of periodontitis in an experimental animal model (rabbit). Methods. In each of 24 rabbits, two experimental periodontal defects were created. In total, 47 defects were treated with open-flap debridement and one of three procedures: (1) GT extracted and soaked with aspirin and omega-3 fatty acids (ASA+OMEGA3 group); (2) GT soaked with saline (PLACEBO group); or (3) GT left untreated (CONTROL group). Then, the GT was replaced in situ. Primary evaluated criteria were the probing pocket depth (PPD) and the clinical attachment level (CAL). Necropsies were harvested 2, 6, and 12 weeks after surgery. The samples were used for histological and molecular biological assessment. Results. A trend of greater PPD and CAL in the ASA+OMEGA3 group was observed at 6 weeks. However, there was no significant difference between them. During the observation period, tissue levels of FGF-7, IL-1β and TIMP-1 showed a statistically significant decrease (P<0.05). For the other variables, the ASA+OMEGA3 group was comparable with the PLACEBO and CONTROL groups. Conclusion. This experiment did not demonstrate the superiority of the proposed approach. However, the enriched granulation tissue did not impair healing outcomes.
Keywords: periodontitis; granulation tissue; oral surgery; inflammation mediators; lipoxin